Developing a meal-planning exchange list for commonly consumed Pakistani dishes - Khan, Imran; Yasmeen, Fatima; Ahmad, Jamil; Abdullah, Aiman; ud Din, Zia; Iqbal, Zafar; Iqbal, Mudassar (Progress in Nutrition, 2019)
In the present study, thirty commonly consumed Pakistani dishes were prepared using standard recipes and analyzed for their proximate composition. Meal planning exchange lists were then developed for those dishes. Significant variations in macronutrient content were observed among the dishes. The fat content varied from 5.2% in chicken biryani to 20.7% in bitter gourd. The protein content ranged from 1.24% in okra to 18.06% in fish while carbohydrate content ranged from 4.83% in fish to 28.9% in simple rice. The energy value ranged from 128 kcal/100 g in haleem to 280.5 kcal/100 g in chapli kabab. Correlation analysis between macronutrient content obtained from proximate analysis and those obtained from nutrient analysis software showed significant correlation for carbohydrate r = 0.80 (P < 0.01) and protein content r = 0.682 (P < 0.01) and non significant correlation for fat content r = 0.295 (P = 0.113). Data from the present study can be used as a meal planning tool by dietitians and nutritionists in planning normal and therapeutic diets. Further research on the nutritional contributions of other traditional dishes in the region is needed.